GAMBARAN PENGETAHUAN, SIKAP, PERSEPSI 1000 HARI PERTAMA KEHIDUPAN SERTA STATUS GIZI PADA CALON PENGANTIN WANITA DI JAKARTA TIMUR : Studi Kualitatif - Intan Permatasari (2020)
Brides is included in women of childbearing age although strictly not included in the target group of the first 1000 days of life (HPK), but the nutritional status of women of childbearing age contributes significantly to health during pregnancy and birth. Not only nutritional status, knowledge, attitudes, perceptions of the first 1000 days of a good life are needed to prepare themselves as future mothers. The purpose of this study to describe of knowledge, attitudes and also perceptions regarding the first 1000 days of life, nutritional status and factors that influence knowledge, attitudes and perceptions regarding the first 1000 days of life of the bride-to-be in Makasar, East Jakarta. This research uses the qualitative methods, taken by purposive sample and Snowball, there were 18 main informants. The results showed that most of the informant's nutritional status was normal, most of the informants showed positive and good attitudes and perceptions, but still needed the right knowledge, because the knowledge of the informant was still included in the know level, therefore still needed additional information from the right source, and there are several factors that influence the environment (colleagues, family and media) as well as the motivation and desire of the bride.